СПЕЦИФІКА ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛІВ АНГЛІЙСЬКОЇ МОВИ У СТОКГОЛЬМСЬКОМУ УНІВЕРСИТЕТІШВЕЦІЇ - Сілютіна, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Розглянута програма підготовки вчителів англійської мови Стокгольмського університету. Охарактеризовано зміст та головні цілі професійної підготовки вчителів англійської мови, як складової педагогічної освіти і вищої освіти країни. Спеціалізації, як правило, вирізняються високою конкретністю. Проаналізовано обов’язкові компоненти підготовки вчителів англійської мови а також широкий спектр магістерських програм завдяки яким професіоналізм вчителя є сукупністю знань, умінь і цінностей, які зумовлені професійною та освітньою діяльністю. Рассмотрена программа подготовки учителей английского языка Стокгольмского университета. Охарактеризованы содержание и главные цели профессиональной подготовки учителей английского языка, как составляющей педагогического образования и высшего образования страны. Проанализированы обязательные компоненты подготовки учителей английского языка а также широкий спектр магистерских программ благодаря которым профессионализм учителя является совокупностью знаний, умений и ценностей, обусловленных профессиональной и образовательной деятельностью. Considered training program for teachers of English Stockholm University. The characteristic content and main goals of training teachers of English as a component of teacher education and higher education in the country. Restructuring of teacher education in Sweden are also the focus of special attention of the government and society in general. The determining factors for effective preparation of acts certainty content of training regulations state documents. The priority focus of modern Swedish universities for improving the training of teachers of foreign languagesis the individualization of learning and the creation of optimal methods of teaching foreign languages, which will form a stable communicative speech skills. Specializations are generally characterized by high specificity. Analyzed components required training English teachers and a wide range of master’s programs through which professional teacher is a combination of knowledge, skills and values that are caused by occupational and educational activities. Professional training English teachers carried out in the Faculty of Humanities at Stockholm University is making it the largest Faculty of Humanities in Sweden. Research at the University of searching for prospective students: when placed on a powerful material and technical base. Graduates are not only knowledge but also know exactly how, when and where they can be used. The components of an effective system of training of teachers is to encourage the development of a common approach in education and cooperation of teachers of different specializations.